MOTIVE OF THE 'RAN AWAY' OF STUDENTS IN ONE OF THE TAHFIZ ISLAMIC BOARDING SCHOOL IN BOGOR - Anwar; Said Ma’ruf (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This research aims to find out to what extent the motives of students at the Tahfiz Al-Qur'an Islamic boarding school who often “ran away”, both at night and in the morning. Even though regulations and sanctions have been implemented, the deterrent effect on students has not made any changes. This research uses a qualitative method with a phenomenological approach which is used to understand the "run away" motives of students. Interviews were conducted with 5 students representing middle and high school levels at one of the Tahfiz Islamic boarding schools in the city of Bogor. The results of interviews with the "ran away" students showed that they had been studying or boarding for eleven months to three years. The students admitted that they felt bored and uncomfortable at the boarding school because of the lack of facilities and monotonous activities, as well as the lack of attention and appreciation from the supervisors at the boarding school. They often "run away" because they feel less fulfilled and did not get enough attention. Positive feedback and attention from coaches or teachers can increase their intrinsic motivation but it is still not optimal